Avaliação e critério para a utilização de semeadora com sistema de taxa variável de sementes na cultura da soja - Uhry, Daniel (2013)
Precision agriculture (PA) is an activity considered quite recent and many studies have been conducted in this area. New technologies towards AP were made available over a short time and should be better studied, in order to prove their contribution to production systems. Among the new technologies, planters with variable seed and fertilizer metering systems are being developed. On these machines, the driving of feeder mechanisms is done by a hydraulic motor powered by power take off (PTO) or by tractor s hydraulic system itself. It is assumed that different ways of driving the feeder system in seeders can cause different demands of tractor power, and influence the performance of the whole tractor-planter system and even longitudinal distribution of seeds. One of the goals of this study was to evaluate the performance of planter and tractor system, working three different speeds. Another goal was to determine whether terrain relief can be used as a parameter to use variable rate of seeds in soybean culture. An experiment varying sowing density on different terrain relief aiming improved grain productivity was designed. Two experiments were conducted at the farm Limburgia, belonging to Van Ass Seeds, in the municipality of Palmeira das Missões, Rio Grande do Sul. For the first experiment, the tractor planter system was tested in three speeds evaluating tractor slippage, tractive force and fuel consumption; initial and final plant stand as well as seed longitudinal distribution and grain productivity were evaluated. As a result it was found that the variation in operation speed did not influence the tractive force, tractor wheel slippage nor fuel consumption or soybean grain productivity. In the second experiment, the behavior of two soybean cultivars, in five planting densities at three locations (top, hillside and plains), was evaluated in irrigated area by center pivot. Initial stand of plants, soil water availability over the cycle, final stand of plants and productivity were evaluated. Grain productivity differed due to terrain position and according to the cultivars tested. Referring to this experiment the relief can be used as a factor in decision making, concerning the use of variable seed rate in soybean sowing.